The Information of Government’s Social Media and Websites to Citizen Engagement in Indonesia - Ernungtyas, Niken Febrina; Boer, Rino Febrianno (Mediator: Jurnal Komunikasi, 2023)
Social media and government websites can become communication tools to encourage participation and interaction between citizens and government institutions. Digital media may lead to citizens’ trust and citizen engagement toward the government. The purpose of this study is to examine the model of attention to social media, attention to official government websites, perceptions of transparency, public trust, and civic engagement in the Indonesian context. This study used a quantitative survey approach (N = 263). Structural Equation Modeling – Partial Least Square (SEM) is used to assess four hypotheses. This study reveals that Attention to Social Media and Attention to Government Websites moderately explain the influence on Perceived Transparency. Moreover, perceived transparency significantly and strongly influences citizens’ trust and Citizen Engagement is quite stronger explained by the Citizen Trust. This study reveals that the information exposure on the government website and social media leads to citizen engagement mediated by the perceived transparency and citizens’ trust.